Aesthetic rehabilitation of a complicated crown-root fracture of the maxillary incisor: combination of orthodontic and implant treatment - Avila, Érica Dorigatti de [UNESP]; Molon, Rafael Scaf de [UNESP]; Cardoso, Mauricio de Almeida; Capelozza Filho, Leopoldino; Campos Velo, Marilia Mattar de Amoêdo; Mollo Júnior, Francisco de Assis [UNESP]; Borelli Barros, Luiz Antonio [UNESP] (Hindawi, 2014)
The aim of this paper is to present a complex rehabilitation, of fractured tooth, with implants in anterior region considering the orthodontics extrusion to clinical success. At 7 years old, the patient fractured the maxillary left central incisor and the dentist did a crown with the fragment. Twenty years later, the patient was referred to a dental clinic for orthodontic treatment, with the chief complaint related to an accentuated deep bite, and a professional started an orthodontic treatment. After sixteen months of orthodontic treatment, tooth 21 fractured. The treatment plan included an orthodontic extrusion of tooth 21 and implant placement. This case has been followed up and the clinical and radiographic examinations show excellence esthetic results and satisfaction of patient. The forced extrusion can be a viable treatment option in the management of crown root fracture of an anterior tooth to gain bone in a vertical direction. This case emphasizes that to achieve the esthetic result a multidisciplinary approach is necessary.